Reestablishing Legitimacy After Corporate Frauds: The Role of Governance Structure in Restoring Financial Credibility in Emerging Economies - Al fartizi, Bassam; Al Hasham, Friedman; Wahab, Ibrahim (Journal Economic Business Innovation, 2024)
Purpose: his research aims to explore the relationship between changes in corporate governance structures and the financial recovery of firms following corporate fraud in emerging markets. The main focus of the research is to understand how governance changes can affect the financial credibility recovery of firms affected by fraud, with a case study of Iraq as an emerging market country.Method: This study uses a quantitative approach with data collected from non-financial companies listed on the Baghdad Stock Exchange. The Baneish M-score model was used to identify companies involved in fraud. A number of statistical methods were used to analyse governance changes and the financial performance of companies.Findings: This study found that firms involved in fraud tended to have weak governance before the fraud was uncovered. However, after the fraud, most firms made significant changes to their governance structure. This led to improved financial recovery of the firms, particularly in terms of financial reporting transparency and increased investor confidence, which in turn improved their market performance.Novelty: This research provides a novel contribution to the understanding of the importance of corporate governance reforms in the recovery process after corporate fraud, particularly in emerging markets such as Iraq. It presents country-specific governance dynamics and provides insights into effective recovery strategies.Implications: The findings of this study provide important insights for policymakers, regulators and business leaders in emerging markets. The research highlights the importance of improved governance and transparency in financial reporting to mitigate the negative impact of corporate fraud and to increase market confidence, which in turn will support the recovery and financial stability of companies involved in fraud.